PERDARAHAN INTRASEREBRAL SEBAGAI KOMPLIKASI NEUROLOGI EMBOLI SEPTIK PADA ENDOKARDITIS INFEKTIF SEBUAH LAPORAN KASUS - Mohammad Kurniawan,* Salim Harris,* Al Rasyid,* Taufik Mesiano,* Rakhmad Hidayat,* Yesi Astri* (NEURONA, 2019)
ENDOCARDITIS IE IS A LIFETHREATENING DISEASE THE INCIDENCE OF IE IN DEVELOPING COUNTRIES IS REPORTED AT 1762 PER 100000 INDIVIDUALS PER YEAR IE IS ALSO KNOWN AS A POTENTIAL CONDITION FOR EMBOLIZATION ESPECIALLY SEPTIC EMBOLISM TO THE BRAIN SEPTIC EMBOLISM RESULTS IN VARIOUS NEUROLOGICAL COMPLICATIONS AND MANIFESTATIONS DUE TO VASCULAR OCCLUSION ANEURYSM FORMATION AND RUPTURE OF THE ANEURYSM